2016
DOI: 10.1016/j.neuropharm.2015.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin potentiates sensitivity to the interoceptive effects of alcohol and increases alcohol self-administration in rats

Abstract: Gabapentin, a drug used in the treatment of epileptic seizures and neuropathic pain, has shown efficacy in the treatment of alcohol dependence. Moreover, given that gabapentin is used in the general population (e.g., non-dependent individuals, social drinkers), we sought to utilize preclinical assessments to examine the effects of gabapentin on sensitivity to moderate alcohol doses and alcohol self-administration in rats with a history of moderate drinking. To this end, we assessed whether gabapentin (0, 10, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Although different paradigms (as well as different species and sexes) were employed, they reported similar findings for the acute effects of gabapentin on drinking. Besheer and colleagues () found that 60 mg/kg gabapentin increased alcohol self‐administration in male rats. Moreover, Besheer and colleagues () further characterized the interoceptive effects of gabapentin and found that 120 mg/kg had alcohol‐like effects and was able to potentiate the discriminative stimulus effects of alcohol (Besheer et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although different paradigms (as well as different species and sexes) were employed, they reported similar findings for the acute effects of gabapentin on drinking. Besheer and colleagues () found that 60 mg/kg gabapentin increased alcohol self‐administration in male rats. Moreover, Besheer and colleagues () further characterized the interoceptive effects of gabapentin and found that 120 mg/kg had alcohol‐like effects and was able to potentiate the discriminative stimulus effects of alcohol (Besheer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Besheer and colleagues () found that 60 mg/kg gabapentin increased alcohol self‐administration in male rats. Moreover, Besheer and colleagues () further characterized the interoceptive effects of gabapentin and found that 120 mg/kg had alcohol‐like effects and was able to potentiate the discriminative stimulus effects of alcohol (Besheer et al, ). In contrast, gabapentin dose‐dependently (900, 1,800 mg/d) decreased alcohol drinking in a 12‐week, double‐blind, placebo‐controlled randomized dose‐ranging trial of adult men and women with current alcohol dependence (Mason et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, acamprosate and the opioid receptor antagonists naltrexone and nalmefene reduce operant oral ethanol self-administration in rats under a variety of conditions (Rassnick et al 1992; Heyser et al 1998; Heyser et al 2003; Sabino et al 2006; Ji et al 2008; Gilpin et al 2008; Walker and Koob 2008) and, analogously, show some efficacy to mitigate alcohol use disorders (see Stevenson et al 2015; Keating 2013; Rösner et al 2010; Plosker 2015; but see Palpacuer et al 2015). Gabapentin reduced both the anxiogenic-like behavior and the increased ethanol self-administration observed in withdrawn, ethanol dependent rats, but not non-dependent rats (Roberto et al 2008; Besheer et al 2016; Watson et al 1997) and was found to improve emotional function and reduce insomnia and alcohol use in abstinent alcoholics (Bonnet et al 2007; Malcolm et al 2007; Brower et al 2008; Myrick et al 2009; Mason et al 2014). Most recently, the glucocorticoid receptor antagonist mifepristone, which like CRF 1 antagonists more efficaciously reduces ethanol intake in dependent rodents during abstinence than in non-dependent rodents (Yang et al 2008; Simms et al 2012; Vendruscolo et al 2012; Vendruscolo et al 2015), was found to reduce alcohol-cued craving in the laboratory as well as naturalistic measures of alcohol use in a double-blind, placebo-controlled study of 56 alcohol-dependent human subjects (NCT01548417; Vendruscolo et al 2015).…”
Section: Performance In Animal Modelsmentioning
confidence: 99%
“…Several studies using drug discrimination procedures have assessed the capacity of gabapentin or pregabalin to substitute for various psychoactive compounds from different pharmacological classes [21-26]. Among them is a double-blind, placebo-controlled, clinical study that found gabapentin capable of full substitution for the cannabinoid CB 1/2 receptor (CB 1/2 R) partial agonist (−)-trans-Δ 9 -tetrahydrocannabinol (Δ 9 -THC) in Cannabis users trained to discriminate ingestion of Δ 9 -THC from ingestion of placebo [26].…”
Section: Editorialmentioning
confidence: 99%